Entrepreneurial network: A case study of business owner in Universiti Utara Malaysia (UUM), Kedah - Mustapa, Azrain Nasyrah (Universiti Utara Malaysia, 2006)
The network construct has been used extensively in entrepreneurship studies.However, while the increasing use of the construct has enhanced our understanding of the phenomenon, its popularity has sometimes led to misconception and inconsistent research findings.Hence the aimed of the research were to determine the difference and relationships of gender, marital status and business experience with entrepreneurial network among business owners in UUM.The research model was adopted from Economic - Psychology Model, which was developed by previous researchers to study the determinants of entrepreneurial network.The research was conducted at Universiti Utara Malaysia (UUM), Kedah.The respondents comprised of a sample of 71 business owners who are currently operating their business in UUM. The questionnaire consisted of two sections, namely demographic factor and entrepreneurial networks.Data were analyzed through Crosstabulation and Ch - Square techniques.Statistic had shown that a majority of the business owners were holding food or catering business.It was found that gender did not influence network activity and size.In addition, network activity had significant differences with respondents’ marital status.Results also showed that single respondents were more active in network activity compared to married respondents.In contrast, network activity and size did not significantly associated with marital status.The studies also yielded evidence suggesting business experience were not significantly associated with network activity and size.Thus, these revelations posed a challenge for policy makers to inculcate, encourage and foster entrepreneurial networks in their entrepreneur development programs.Finally, some suggestions and direction for future researches have been forwarded to facilitate the entrepreneur development programs in the business environment.